Digital Transformation: Framework Development of Tourism Social Entrepreneurship (TSE) - Yustina Chrismardani; Anang Kistyanto; Sanaji Sanaji; Andre Dwijanto Witjaksono (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Change that cannot be avoided by organizations or companies is digital transformation or digitization. Digital transformation also cannot be separated from tourism. Tourism Social Entrepreneurship (TSE) is a tourism development strategy that is centered on society/community. The Tourism Social Entrepreneurship (TSE) framework includes natural, building, financial, political, social, cultural and human capital. Digital transformation can effectively promote the sustainability of cultural integration, tourism. which can then be added as a TSE element. Existing research focuses on the role of digital transformation in community development, but not many have examined and incorporated digital transformation as part of change management, within the TSE framework. Considering the development of digitalization in the world of tourism, this study was carried out by integrating the TSE framework with digital transformation through a change management lens. This research uses a Systematic Literature Review (SLR) with the PRISMA method. It is hoped that the research results will be a scientific contribution to change management, especially in relation to digital transformation and Tourism Social Entrepreneurship.